A comprehensive review on evaporative cooling systems - Kapilan, N.; Isloor, Arun M.; Karinka, Shashikantha (Results in engineering, 2023)
The evaporative cooling system (ECS) is one of the cheapest and oldest cooling technologies. The conventional single stage ECS is most widely used in domestic application, particularly in hot and dry regions. However, in this system, the temperature of the air cannot be reduced below the wet bulb temperature of the air. The multistage ECS system helps to overcome this problem. The combination of direct and indirect ECS helps to reduce the temperature of the air below its wet bulb temperature. The further reduction in air temperature may be achieved with the help of the cooling coil driven by vapour compression system. The energy consumed by the ECS is lower as compared to vapour compression refrigeration system. The ECS can be driven with the help of solar power. The conventional cooling pad used in ECS can be replaced with locally available natural fibers to reduce initial cost and to reduce dependence on import of cooling pads. The performance of the ECS can be improved with the help of heat pipe. Various techniques are used to enhance ECS's performance. The performance of the vapour compression refrigeration system can be improved with the help of ECS. This paper discusses basics and types of ECS, methods used to increase the performance of ECS, types of natural fiber cooling pad material, process variables affecting ECS, recent technical advancements, challenges and opportunities. •Discuss different types of evaporative cooling system.•Critically evaluate different types of cooling pad materials.•Reports the energy saving potential of evaporative cooling system.•Compare the performance of the evaporative cooling system with different cooling pad materials.•Highlights the opportunities and challenges in the area of evaporative cooling system.